Регулювання концентрації амонійного азоту при метановій ферментації курячого посліду в умовах рециркуляції рідкої фази - Шаповалов, Євгеній Борисович; Жадан, Сергій Олександрович; Салюк, Анатолій Іванович; Котинський, Андрій Валерійович (My University, 2018)
In the article an estimation of efficiency of a new method of regulation of ammonia nitrogen concentration during methane fermentation of chicken manure under conditions of liquid phase recirculation is presented. The essence of the method is the absorption of ammonia from the gas phase by non-volatile sorbent, which is located directly in the reactor, but not in contact with the substrate. The modeling of ammonium nitrogen concentration during the production of biogas from chicken manure in semi-continuous mode without ammonia removal and with ammonia removal was carried out. The results obtained in the research of removal of ammonium nitrogen from solutions of ammonium salt, which simulate a substrate with a high concentration of the inhibitor, in the periodic mode were used. Phosphoric acid was used as a sorbent, because it is able to react with ammonia, it is non-volatile, as a result of the reaction, a product that is useful for agriculture is formed. It is accepted that the process is carried out in the thermophilic mode at the temperature of 50°C, the substrate moisture content of 90%, and the hydraulic retention time of 5 and 10 days. The concentration of phosphoric acid was 4 mol/dm3 . The pH of the medium is assumed to be 7.5, 8.0 and 8.5. The ratio of the area of the sorbent and the substrate was 1:4.6, and the diameter of the apparatus and the depth of the substrate — 1:1.5. The maximum degree of the effluent recirculation of 60%, which was used in the modeling, corresponding of full replacement of water, that used to dilute the native chicken manure with moisture content of 75% to moisture content of 90%. Ammonia nitrogen content during liquid phase recirculation under certain conditions was lower than 3000 mg/dm3 , which was taken as a safe level for biogas plant operation. The degree of removal of ammonia nitrogen can be significantly increased by changing the geometric dimensions of the biogas reactor, increasing the contact area of the sorbent with the gas phase and increasing the hydraulic retention time. According to the modeling results, the considered method is sufficiently effective for use in the conditions of liquid phase recirculation. У статті наведено оцінку ефективності нового методу регулювання концентрації інгібітора під час метанової ферментації курячого посліду в умовах рециркуляції рідкої фази. Суть методу полягає у сорбції аміаку з газо- вої фази нелетким сорбентом, який знаходиться безпосередньо в реакторі, але не контактує із субстратом. Проведено моделювання концентрації амонійного азоту під час виробництва біогазу з курячого посліду у напівбез- перервному режимі без вилучення аміаку та з вилученням. При цьому використано результати, отримані при дослідженні видалення амонійного азоту з розчинів солі амонію, що моделюють субстрат з високою концен- трацією інгібітора, у періодичному режимі. Як сорбент була застосована фосфорна кислота, оскільки вона здатна реагувати з аміаком, є нелеткою, у результаті реакції утворюється корисний для сільського господарства продукт. Прийнято, що процес проводиться у термофільному режимі при температурі 50°С, вологості субстрату 90% і гідравлічному часі утримання 5 та 10 діб. Концентрація фосфорної кислоти становить 4 моль/дм3. Значення рН середовища прийнято рівним 7,5, 8,0 і 8,5. Співвідношення площі сорбенту і субстрату становить 1:4,6, а діаметра апарата до глибини субстрату — 1:1,5. Максимальний ступінь рециркуляції стоку 60%, який було використано при моделюванні, відповідає повному заміщенню води, що використовується для розбавлення курячого посліду нативної вологості 75% до вологості 90%. Вміст амонійного азоту при рециркуляції рідкої фази за певних умов був нижчим ніж 3000 мг/дм3, що було прийнято за безпечний для роботи біогазової установки рівень. Ступінь вилучення амонійного азоту може бути суттєво збільшено за рахунок зміни геометричних розмірів біо- газової установки, збільшення площі контакту сорбенту з газовою фазою та гідравлічного часу утримання. Відповідно до результатів моделювання, розглянутий метод є достатньо ефективним для його використання в умовах рециркуляції рідкої фази
Keywords: кафедра харчової хімії; амонійний нітроген; ammonia nitrogen; пташиний послід; chicken manure; рідка фракція; liquid phase; methane fermentation; моделювання; метанова ферментація; modeling; recirculation; рециркуляція